Constructing a stable interfacial phase on single-crystalline Ni-rich cathode via chemical reaction with phosphomolybdic acid. (September 2021) - Zou, Yu-Gang; Meng, Fanqi; Xiao, Dongdong; Sheng, Hang; Chen, Wan-Ping; Meng, Xin-Hai; Du, Ya-Hao; Gu, Lin; Shi, Ji-Lei; Guo, Yu-Guo
Abstract: Ni-rich single-crystalline cathode has been demonstrated to be a promising candidate for next-generation high energy density batteries by solving intergranular cracks occurring in its counterpart consisting of aggregated small primary particles. However, the inherently unstable surface nature of Ni-rich cathodes, such as rock-salt phase transition, reactive oxygen release, and parasitic side reactions, has not been solved, which would deteriorate the electrochemical performance of single-crystalline Ni-rich cathode. To further improve the durability, these surface issues should be urgently mitigated. Herein, we proffer a simple yet effective method to regulate the surface chemical composition and property of single-crystalline LiNi0.8 Co0.1 Mn0.1 O2 via phosphomolybdic acid treating. This novel surface treating method successfully suppressed rock-salt phase transformation and (cathode electrolyte interphase) CEI growth during cycling. As a result, the as-obtained LiNi0.8 Co0.1 Mn0.1 O2 cathode exhibits excellent capacity retention of 92% after 200 cycles at 0.5 C. Also, a remarkable enhancement of thermal stability was achieved. This work demonstrates the great potential of surface modification strategy for Ni-rich single-crystalline cathode and would pave the way for its implementation. Graphical Abstract: ga1 Phosphomolybdic acid treating and high-temperature sintering were developed to remedy the vulnerability of the surface of the single-crystalline Ni-rich cathode. With this method, consuming lithium residues, forming Li + conductor, and reconstructing rock-salt phase were simultaneously achieved. This new regulated surface greatly mitigated the rock-salt phase transition, CEI growth, and LiPF6 decomposition during cycling. As a result, the durability of the single-crystalline Ni-rich cathode was remarkably improved without any loss of capacity and rate capability. Highlights: An effective strategy simultaneously consuming lithium residues, forming Li + conductor, and reconstructing the surface structure was designed to remedy the vulnerability of the surface of single-crystalline Ni-rich cathode. The regulated surface mitigates LiPF6 decomposition, CEI growth, and rock-salt phase transition at the surface during cycling. The as-obtained cathode shows excellent capacity retention and thermal stability.